The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1038/pj.2011.6
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between solvent treatment and the microstructure of PAN-b-PEG copolymer membranes

Abstract: Block copolymer membranes consisting of thiophene-permselective components for use in gasoline desulfurization were prepared by the copolymerization of polyethylene glycol (PEG) with acrylonitrile by water-phase precipitation copolymerization. In this study, a solvent annealing treatment was applied to evaluate the microdomain orientation and the affinity between polyacrylonitrile-block-polyethylene glycol (PAN-b-PEG) copolymers and solvents. Using atomic force microscopy, appreciable microphase separation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Figure shows clearly that compared to the pristine PVDF membrane whose water contact angle was changed from 95° to 87° in 600 s, the water contact angle of PVDF‐g‐PNIPAAm membrane descended obviously. When the reaction time was 36 h, the water contact angle decreased to 50° after 600 s. It was indicated that the hydrophilicity of the grafted membrane was improved, and with the reaction time increased [], the hydrophilicity of the modified membrane improved gradually. It corresponded to the results of XPS, and the reaction time of 36 h was in favor of surface‐initiated ATRP.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows clearly that compared to the pristine PVDF membrane whose water contact angle was changed from 95° to 87° in 600 s, the water contact angle of PVDF‐g‐PNIPAAm membrane descended obviously. When the reaction time was 36 h, the water contact angle decreased to 50° after 600 s. It was indicated that the hydrophilicity of the grafted membrane was improved, and with the reaction time increased [], the hydrophilicity of the modified membrane improved gradually. It corresponded to the results of XPS, and the reaction time of 36 h was in favor of surface‐initiated ATRP.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the PDMS, PEG can also act as an appropriate membrane material for pervaporation desulfurization of gasoline in accordance with the methodology outlined in the solubility parameter theory. Kong et al [74,78] created PEG-b-PAN membranes based on dispersed PEG micro domains and bulk PAN phases. In this case, an increase in the total flux and a decrease in sulfur enrichment factor were attained by either lowering PEG molecular weight or by increasing PEG mass content value that caused greater proportion of PEG micro domains.…”
Section: Clean Gasolinementioning
confidence: 99%